How a Coding Error Sparked Short-Term Reform at a Custodial Mental Hospital - Sommer, Robert (Action Learning and Action Research Journal, 2013)
This article highlights the important role played by the research consultant in action research (AR) with organizations lacking experience in behavioural research. In this case, the consultant helped staff of a custodial mental hospital conduct a community survey. When the consultant departed, hospital staff did not realize that questionnaire items had been counterbalanced. The uproar created by the incorrectly scored items, which cast the hospital in a negative light, resulted in several positive reforms. Without further prodding, most of the reforms proved temporary.